Between-rater reliability for using radar technology to quantify maximal horizontal deceleration performance in NCAA division 1 American football and female lacrosse athletes - Philipp, N. M.; McKay, B.; Martin, E.; Cabarkapa, D.; Fry, A. C.; Troester, J. (Frontiers in Sports and Active Living, 2024)
Introduction: With recent increases in the popularity of studying the physical construct of horizontal deceleration performance in team-sport athletes, the aim of the present study was to assess the inter-rater and intra-rater reliability of processing and quantifying horizontal deceleration ability using radar technology.